Status and change of tree crown condition at the CONECOFOR plots, 1996 - 2005 - Bussotti, Filippo; Calderisi, Marco; Cenni, Enrico; Cozzi, Alberto; Bettini, Davide; Ferretti, Marco (Annals of Silvicultural Research, 2013)
Between 1996 and 2005 crown condition at Italian Level II plots was assessed annually within the CONECOFOR programme. Three different assessment forms and manuals were adopted over this period of time (the first in 1996-97, the second between 1998 and 2004, the last starting in 2005); as a result, many of the parameters investigated and the data collected are neither homogeneous nor comparable over time. Since, however, neither the definition nor the assessment criteria for transparency changed, this parameter was chosen to represent crown condition variations over time. (In this survey, transparency is used as a proxy for defoliation.) Yearly field surveys were always preceded by an inter-calibration course, and were followed up by Quality Control surveys done by one or more Reference Teams. After 10 years, the results suggest that statistically significant variations in transparency, from one year to the next, are only scattered and display no recognizable trend. Overall, there were 15 variations, of which 7 were positive (i.e. increase in transparency), and 8 negative (i.e. decrease in transparency). The majority of variations is concentrated in the 1997-98 period. Significant defoliation trends were identified in 11 out of the 27 considered plots. In 4 cases these trends were positive (increased transparency).